Analisis Tingkat Kepentingan dan Kinerja Atribut-atribut Daging Sapi Bali yang Beredar di Kota Kupang Provinsi Nusa Tenggara Timur - C R V. Tafuli; B Hartono; B A Nugroho (Universitas Sebelas Maret (UNS), 2013)
The objective was to understand the attributes considered by consumer when deciding to purchase the beef cattle in Kupang, East Nusa Tenggara. As much as 150 respondents were determined using the Accidental Sampling method. There were 100 respondents of final consumer and 50 respondents of business consumer (30 restaurants respondent and 20 hotels respondent). Consumer satisfaction data was analyzed by IPA (Importance Performance Analysis). The Result of Analysis indicates that four indicators, such as product, price, place/distribution, and promotion, were remaining in the quadrant 2 (high performance and importance). The indicator of product had the highest performance and importance compared to price, place/distribution and promotion. the attributes considered by the beef consumer at Kupang City were: a) attributes of product such as lipid content, aroma, texture, package, cutting tidiness, weight size and meat part; b) attributes of price such as price rate, payment method and price discount; c) attributes of place/distribution such as distance, order timing, supply continuity, sale location and storage method; and d) attributes of promotion such as good relationship and direct marketing.Key words: beef cattle attributes, beef cattle consumers, importance performance analysis